ENERGY AND EXERGY EFFICIENCY ANALYSIS OF COMBINED HEAT AND POWER PLANT - Volianska, Larysa; Pikul, Marina (Science-based technologies, 2019)
The article provides energy and exergy analysis of the combined heat and power plant. Exergy analysis is based on the interaction of the system with the environment. This contributes to a more accurate study of the power plant, the identification of nodes with the greatest losses. For the study, the heating scheme of the Darnitsa CHPP was selected. For calculations, we took a chain of a technological scheme consisting of a boiler, a turbine with two selections for heating and production needs, a condenser and a pump. Energy and exergy analyzes were carried out of the operating parameters of the equipment of the Darnitsa CHPP, points with the highest energy losses were identified. A quantitative assessment of energy losses was carried out regardless of the nature of the source of their occurrence. The obtained calculated characteristics for exergy and energy analysis show the distribution of energy losses both in individual nodes and for the system as a whole. The article provides comparative calculations and a graphical comparison of the efficiency and energy and exergy losses at different station loads. It is shown that as a result of such an analysis, all energy transformations occurring in the technological chain of the cogeneration plant are objectively reflected, which serves as the basis for the development of measures to improve the system under study and its optimization. It is shown that the optimization of any parameters of the real installation cycle does not consist in achieving the maximum of its exergy efficiency, but in finding the most economically advantageous solution. Not every installation with the greatest losses is subject to modernization. For example, energy analysis indicates that large losses occur in the capacitor. At the same time, an exergy analysis shows that with these environmental parameters, an improvement in the capacitor will not lead to an increase in efficiency.